PENGARUH FAKTOR SOSIAL EKONOMI TERHADAP KEPUTUSAN WANITA UNTUK BER-KB DI PROVINSI SUMATERA BARAT - Anisa Febrina; Novya Zulva Riani (Universitas Negeri Padang, 2015)
The purpose of this study was aim to: (1) household income effects on woman’s choice using “KB”, (2) mother’s education effects on woman’s choice using “KB, and (3) total household member effects on woman’s choice using “KB” in West Sumatera Province. This study used secondary data from Survey Sosial Ekonomi Nasional with totaled 2133 samples. The analyses technique are logistic regression analyses. The result showed that: (1) household income has an unsignificant effect on woman’s choice using “KB”, (2) mother’s education has significant effect on woman’s choice using “KB”, (3) total household member has an unsignificant effect on woman’s choice using “KB”, (4) mother’s age has a negative effect on woman’s choice using “KB”, household income, mother’s education, total household member and mother’s age has a positive effect parcially on woman’s choice using “KB”.Keyword : household income, mother’s education, household member, mother’s age